The Role of ASEAN's Rice Commodity Market Integration in Economic Stability and Food Security - Daliani, Hanni Rizki; Amelia, Siska; Suri, Siti Atikah; Safitri, Anita; Nasihah, Arini; Meliana; Hasmidyani, Dwi; Budiman, Muhammad Akbar (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2024)
Food security is a crucial issue in economics, particularly for ASEAN countries that heavily rely on rice commodities. Climate change impacts rice production, leading to production declines and price spikes, threatening economic stability and social welfare. ASEAN has committed to strategic cooperation to protect rice supplies and prevent food crises, while increasing production and stabilizing supply through collaborative initiatives. This study employs qualitative methods and descriptive analysis in literature review to explore the implementation of ASEAN regional cooperation on rice commodities. Secondary data is utilized to understand the impact of rice commodities on food security in the ASEAN region. Through a descriptive analytical approach, this research aims to provide an accurate picture of the relationship between regional cooperation and rice commodity management in ASEAN. The results indicate that ASEAN rice market integration is vital to reduce price risks for farmers and improve food security. The establishment of a rice futures market can help manage risks and ensure stable prices, which are crucial for maintaining economic stability. Regional cooperation and harmonization of rice standards are necessary, along with improved infrastructure and financial support for farmers to sustain the agricultural sector and the economic well-being of the ASEAN region.